Mobility and transformation of CdSe/ZnS quantum dots in soil: Role of the capping ligands and ageing effect. (September 2020) - Carboni, A.; Gelabert, A.; Charron, G.; Faucher, S.; Lespes, G.; Sivry, Y.; Benedetti, M.F.
Abstract: The increasing application of Quantum Dots (QDs) is cause of concern for the potential negative effects for the ecosystem, especially in soils that may act as a sink. In this study, soil leaching experiments were performed in quartz sand packed columns to investigate the behavior of core-shell CdSe/ZnS QDs coated with either small ligands (TGA-QDs) or more complex polymers (POAMA-QDs). Fluorescence emission was compared to mass spectrometric measurements to assess the nanoparticles (NPs) state in both the leachate (transported species) and porous media (deposited amounts). Although both QDs were strongly retained in the column, large differences were observed depending on their capping ligand stability. Specifically, for TGA-QDs elution was negligible and the retained fraction accumulated in the top-columns. Furthermore, 74% of the NPs were degraded and 38% of the Se was found in the leachate in non-NPs state. Conversely, POAMA-QDs were recovered to a larger extent (78.1%), and displayed a higher transport along the soil profile. Further experiments with altered NPs showed that homo-aggregation of the QDs prior injection determined a reduced mobility but no significant changes in their stability. Eventually, ageing of the NPs in the column (15 days) caused the disruption of up to 92% of the original QDs and the immobilization of NPs and metals. These results indicate that QDs will accumulate in top-soils, where transformations phenomena will determine the overall transport, persistency and degradation of these chemicals. Once accumulated, they may act as a source for potentially toxic Cd and Se metal species displaying enhanced mobility. Graphical abstract: Image 1 Highlights: CdSe/ZnS quantum dots displayed high deposition and limited mobility in quartz sand. Nanoparticles transformation and degradation occurred during transport experiments. Up to 38% of the metals was found in the leachate in non-nanoparticles form. Ageing of the nanoparticles enhanced retention and transformation.